Pulse oximetry in the newborn: Is the left hand pre- or post-ductal? - Bucher Hans; Rüegger Christoph; Mieth Romaine (BMC, 2010)
Abstract Background Over the past few years, great efforts have been made to screen duct-dependent congenital heart diseases in the newborn. Arterial pulse oximetry screening (foot and/or right hand) has been put forth as the most useful strategy to prevent circulatory collapse. The left hand, however, has always been ignored, as it was unclear if the ductus arteriosus influences left-hand arterial perfusion. The objective of our study was to evaluate the impact of the arterial duct on neonatal pulse oximetry saturation (POS) on the left hand. Methods In this observational study, arterial oxygen saturation on both hands and on one foot was measured within the first 4 hours of life. Results Two hundred fifty-one newborns were studied: 53% males and 47% were delivered by caesarean section. The median gestational age was 38 4/7 weeks (90% CI, 32 6/7 - 41 2/7 weeks), the median birth weight was 3140 g (90% CI, 1655 - 4110 g) and the median age at recording was 60 minutes (90% CI, 15 - 210 minutes). The mean POS for the overall study population was 95.7% (90% CI, 90 - 100%) on the right hand, 95.7% (90% CI, 90 - 100%) on the left hand, and 94.9% (90% CI, 86 - 100%) on the foot. Four subgroups (preterm infants, babies with respiratory disorders, neonates delivered by caesarean section, and newborns ≤15 minutes of age) were formed and analysed separately. None of the subgroups showed a statistically significant difference between the right and left hands. Additionally, multivariate logistic regression did not identify any associated factors influencing the POS on the left hand. Conclusions With the exception of some children with complex or duct dependent congenital heart defects and some children with persistent pulmonary hypertension, POS on both hands can be considered equally pre-ductal.